Study of the seasonal variations of the fatty acid profiles of selected macroalgae - Pereira, Tatiana (2021)
Due to the high consumption of fat-rich processed foods, efforts are being done to reduce their saturated fat (SFA) contents and replace it with polyunsaturated fatty acids (PUFA), creating a necessity to find alternative PUFA sources. Macroalgae, being a promising natural source of healthy food, may be such an alternative. The fatty acid (FA) profile of Fucus spiralis, Bifurcaria bifurcata, Ulva lactuca, and Saccorhiza polyschides were determined through direct transesterification and their seasonal variation was studied. F. spiralis showed the highest FA content overall, B. bifurcata presented the higher PUFA amounts, and U. lactuca and S. polyschides the higher SFA. The production of FA was shown to be influenced by the seasons. Spring and summer seemed to induce the FA production in F. spiralis and B. bifurcata while in U. lactuca the same was verified in winter. U. lactuca presented a !6/!3 ratio between 0.59 and 1.38 while B. bifurcata presented a ratio around 1.31. The study on the seasonal variations of the macroalgal FA profile can be helpful to understand the best season to yield FA of interest, such as ALA, EPA, and DHA. It may also provide valuable information on the best culturing conditions for the production of desired FAs.